BIO-EFFICACY OF QGU42 10% OD (OXATHIAPIPROLIN): A NEW MOLECULE FOR MANAGEMENT OF LATE BLIGHT OF POTATO IN INDIA - Sharma, Sanjeev (Potato Journal, 2019)
Potato J (2018) 45 (2): 93-98 Sanjeev Sharma1 and Uma Maheshwari2 ABSTRACT: Late blight, caused by an oomycete Phytophthora infestans, is responsible for serious yield reduction in potato throughout the world. Application of effective fungicides continues to be a viable component in developing integrated disease management programme. The build-up of resistance to single-site oomycides has accelerated the research for antioomycete compounds with new modes of action. This study was conducted to evaluate a new chemical, oxathiapiprolin, as foliar application for management of late blight of potato during 2012 and 2013 crop seasons at ICAR-CPRI, Shimla and ICAR-CPRS, Ooty. Four doses of QGU42 10% OD (oxathiapiprolin) @ 150, 200, 250 & 300 ml/ha along with two standard checks were evaluated for its efficacy against late blight of potato and for phytotoxicity. Minimum terminal disease severity (40% & 45%) at both the locations was recorded in plots treated with QGU42 10% OD @300 ml/ha and it was at par with QGU42 10% OD @250 ml/ha and QGU42 10% OD @200 ml/ha. No phytotoxic effects on the foliage were seen at either of the location in any of the treatment doses.